Biological agents for severe asthma: the evolution of the at-home self-injection approach. Issue 4 (August 2020) - Lombardi, Carlo; Bagnasco, Diego; Passalacqua, Giovanni
Abstract : Purpose of review: New biological agents, in addition to the well-established omalizumab, have been nowadays introduced into clinical practice for severe asthma. This suggested the possibility of an at-home self-administration, as currently happening for other biological agents for immune-mediated diseases. Recent findings: In the very recent years, there were structured clinical trials investigating the self at home administrations of biologicals for severe asthma, showing with different principles, a possible advantage and convenience for the patient, and a socioeconomic saving. Summary: The literature analysis currently shows that the at-home self-administration of biologicals for severe asthma is a promising approach to improve the treatment of such disease.